أثر الإعلامية والمقروئية في استيعاب النصوص الأدبية لدى طلبة الجامعات الماليزية - Mohd Ikhwan bin Abdullah (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2018)
This study was designed to investigate the moderative effect of informativity in the relationship between readability and comprehension as well as the effect of informativity on readability. This is due to the fact that informativity leads to high processing of information because of discrepancies and gaps in the structure of texts in which lead to the difficulty of texts. The study also aimed to explore how readers interacted with high informativity texts and its aspects of difficulty. The mixed methods approach was used in this study. Data were collected from 150 final year students from 6 universities in Malaysia. They were divided into two groups. Two types of texts were selected, one of them has intermediate informativity while the other was high in informativity but both were rated the same grade according to Arabic Automated Readability Index (AARI). The first group read the intermediate informativity text while the other read the high informativity text. The participants, next, completed a Cloze test and a summary task. Regression analysis results showed that readability using the Cloze test was a good predictor of comprehension, with R2 at 0.65. However, this result was obtained before taking informativity level into consideration. The interaction effect result showed that the high informativity text was more difficult in terms of comprehension with slope b = 0.36 than intermediate informativity text with slope b = 1.53. It means that both texts should not be at the same level of readability as determined by AARI results. t-test result showed that there was a significant difference in the means of Cloze test scores between intermediate informativity and high informativity texts. The study also provided strong evidence that participants could recall central ideas better than non-central ideas for both texts, but the reliance on inference was higher in the high informativity text. Qualitative analysis showed that high informativity texts required depth-processing due to the quantity of inference load that was found in the samples' summarized texts. Based on these results, the study asserts that informativity should be taken into consideration in measuring the readability of literary texts. Practical and theoretical implications were discussed.